SDN based network resource selection multi-objective optimization algorithm - Nan BAO; Jiakuo ZUO; Han HU; Xu BAO (Tongxin xuebao)
For the problem of coexistence of different resource utility objectives and mutual influence of resource selection strategies in the complex structure of software-defined network (SDN),an SDN based network resource selection multi-objective optimization algorithm was proposed.The optimization goals of resource providers and clients were taken into account in the algorithm,and a resource selection multi-objective optimization model was constructed.The model was further solved by the reference vector based multi-objective optimization algorithm.Simulation results show that compared with other algorithms,the proposed algorithm could quickly converge to the uniformly distributed non-inferior solution set,and balance the optimization objects of multi-party in SDN based resource access management.